Digital marketing management : a handbook for the current (or future) CEO - Zahay, Debra L. (Digital and social media marketing and advertising collection., 2015)
This book is for managers and would-be managers who need to upgrade their knowledge of digital marketing. Told from the perspective of marketing strategy, it puts digital marketing in the context of rm strategy selection. The rst step in digital marketing is to understand your company and your brand. The second step is to put content and keywords on your website so that they can be found in search. Third, use the other delivery platforms of digital marketing, e-mail, social, and mobile, to deploy that content to the customer. The nal topics in the book focus on the importance of data man.